THE SIGNIFICANCE OF WRESTLING SPORTS FOR SOCIETY AND THE HISTORY OF ITS FORMATION (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article talks about the importance of wrestling for society and the history of its formation. A society with increased attention to sports develops in the style of a healthy society. There are all types of sports, which serve not only physical fitness, but also spiritual development of a person. In particular, wrestling is a defense of national values and it ensures the strengthening of national pride and confidence in a bright future.